Reexpanzní edém plíce po drenáži dlouhotrvajícího spontánního pneumotoraxu - kazuistika - Myšíková, D; Simonek, J; Stolz, A; Lischke, R (Rozhledy v chirurgii, 2013)
Reexpansion pulmonary oedema is a rare but possibly lethal complication of thoracic drainage for pneumothorax. Morbidity and mortality of this complication remains high (up to 20% of lethal cases) and as such deserves our attention. We report a case of ipsilateral left-sided pulmonary oedema following chest tube insertion in a 42-year-old male patient with spontaneous pneumothorax. Pneumothorax can be expected to last for up to 3 weeks (from the first presentation of sudden dyspnoea and chest pain). The pathophysiology of this lung affection has not yet been completely elucidated; the crucial role is probably played by damage to the endothelium which is followed by increased endothelial permeability during ischemia-reperfusion injury in a rapidly reexpanding lung. The main risk factors for the development of RPE are young age (the younger the patient, the higher the risk), the female sex, the degree of lung collapse, a pneumothorax that lasts more than 24 hours, a reexpansion of the lung in less than ten minutes, the use of a suction system, and - in cases of a pleural effusion - an evacuation volume of more than 2000 ml. Although in patients with these risk factors the administration of initial negative pressure should be avoided, this procedure remains common practice in pneumothorax treatment in the Czech Republic. Thoracic surgeons are more likely to use the suction system than pulmonologists (70% versus 52%). RPE manifestation ranges from benign clinical course (patients are free of complaints with only pathological chest radiography findings) to potentially lethal rapid respiratory failure with circulatory shock. Most patients develop RPE within 1 hour of expansion and the ipsilateral lung is affected. Only rarely can pulmonary oedema be bilateral, or in the contra-lateral lung. Treatment of RPE is supportive and depends on the individual patients condition, ranging from mere monitoring to mechanical ventilation for serious cases. Positive pressure mechanical ventilation and the utilization of positive end-expiratory pressure (PEEP) remains the gold standard of treatment.
Keywords: Drainage; drenáž; Pulmonary Edema; plicní edém; mužské pohlaví; torakotomie; pneumotorax; dospělí; Humans; Adult; Czech Republic; Pneumothorax; Thoracotomy; lidé; Male; Česká republika